2022
DOI: 10.1002/jcph.2015
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Baseline Use of Angiotensin‐Converting Enzyme Inhibitors and Angiotensin Receptor Blockers and Death Among Patients Tested for COVID‐19

Abstract: Angiotensin-converting enzyme inhibitor (ACEI) and angiotensin receptor blocker (ARB) drugs may modify risk associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Therefore, we assessed whether baseline therapy with ACEIs or ARBs was associated with lower mortality, respiratory failure (noninvasive ventilation or intubation), and renal failure (new renal replacement therapy) in SARS-CoV-2-positive patients. This retrospective registry-based observational cohort study used data from a nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Our results are in the line with the results of multiple published studies that reported that the use of RAAS inhibitors is not associated with increased short-term mortality in COVID-19 patients [17,18]. Our results that suggested a protective effect of ACEIs and ARBs are also consistent with the results of a growing number of studies that associated their use in COVID-19 patients a lower risk of mortality [19][20][21][22]. Furthermore, the benefits of ACEIs and ARBs are not limited to the risk of mortality and the outcomes of severity such as ICU admission and use of ventilators.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in the line with the results of multiple published studies that reported that the use of RAAS inhibitors is not associated with increased short-term mortality in COVID-19 patients [17,18]. Our results that suggested a protective effect of ACEIs and ARBs are also consistent with the results of a growing number of studies that associated their use in COVID-19 patients a lower risk of mortality [19][20][21][22]. Furthermore, the benefits of ACEIs and ARBs are not limited to the risk of mortality and the outcomes of severity such as ICU admission and use of ventilators.…”
Section: Discussionsupporting
confidence: 92%
“…In 197 hospitals across the US, symptomatic emergency department patients were collected; renal failure occurred in 548/13,813 (4.0%) and respiratory failure in 2,485/13,880 (17.9%) patients. In SARS-CoV-2-positive patients, baseline ACEi/ARB was linked to a 25% reduced mortality rate after controlling for these covariates [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…Interestingly, angiotensin receptor blockers (ARBs) and angiotensin-converting enzyme inhibitors (ACEIs), which increase ACE2 expression, were initially involved in the pathogenesis of SARS-CoV-2 infection, and seem nowadays to be defensive against Covid-19 severity (Thomas et al 2022 ). Similarly, ibuprofen which upregulates ACE2 expression displayed a defensive effect against Covid-19 infection (Poutoglidou et al 2021 ).…”
Section: Fxr and Covid-19mentioning
confidence: 99%